Quality Of Life For Adolescents With Divorced Parents On Physical And Psychological Conditions In Indonesia: Literature Review - Haq, Vierthycia Izzatul; Wicaksono, Dimas B. C. (Jurnal Riset Kesehatan, 2023)
Quality of life can be interpreted as a person's view of life related to culture, values, and other factors. The quality of life of adolescents in Indonesia can be influenced by various factors, such as family. Families with divorced parents must experience differences and changes from families with intact parents. The purpose of this study was to describe the quality of life of adolescents in terms of physical and psychological conditions with divorced parents in Indonesia. The research method used in this research is Literature Review. The search for journal articles used 4 databases with a combination of the PICO(S) components and met the inclusion criteria so that 31 articles were extracted according to the research objectives. The results of the analysis show that the quality of life of adolescents with divorced parents depends on each of these adolescents. Physical condition can be seen from the components of pain and discomfort, energy and fatigue, and sleep and rest. And psychological conditions can be seen from the components of positive feeling, thinking, learning, memory, and concentration, negative feelings, self-esteem, and spirituality personal belief.